The Recipe for Delight: An Empirical Study of Customer Satisfaction in the Fast-Food Industry - Odebunmi Abayomi Tunde; Zi Jian Oh; Tat Cong Yap; Wee Na Yap; Yashwini A/P Parthiben; Yasmin Husna Binti Amizi; Tian Ye; Anees Jane Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Subway has established itself as one of the leading fast-food chains in Malaysia by offering customizable sandwiches and promoting a fresh, healthy image. However, customer satisfaction in the fast-food sector is shaped by multiple factors, including price, product quality, promotional effectiveness, and perceived convenience, all of which determine customer loyalty and competitiveness. This study aims to investigate how these factors influence satisfaction with Subway in Malaysia. Data were collected from 110 respondents through an online survey distributed via Google Forms and analyzed using SPSS regression analysis. The results demonstrate that perceived convenience (? = 0.459, p 0.001) and price (? = 0.218, p 0.05) significantly enhance customer satisfaction, jointly explaining 49.9% of the variance (R² = 0.499). In contrast, product (? = 0.099, p 0.05) and promotion (? = 0.043, p 0.05) showed no significant effect, indicating that customers may treat them as standard expectations rather than decisive factors. These findings suggest that Subway should prioritize improving convenience through efficient service channels and digital solutions while maintaining competitive pricing strategies. Innovations in product and promotion remain important to sustain differentiation and strengthen long-term customer loyalty